Antiplasmodial activity of tick defensins in a mouse model of malaria - Couto, Joana; Tonk, Miray; Ferrolho, Joana; Antunes, Sandra; Vilcinskas, Andreas; de la Fuente, José; Domingos, Ana; Cabezas-Cruz, Alejandro (Ticks and tick-borne diseases, 2018)
Malaria is a mosquito-borne disease affecting millions of people mainly in Sub-Saharan Africa, Asia and some South American countries. Drug resistance to first-line antimalarial drugs (e.g. chloroquine, sulfadoxine-pyrimethamine and artemisinin) is a major constrain in malaria control. Antimicrobial peptides (AMPs) have shown promising results in controlling Plasmodium spp. parasitemia in in vitro and in vivo models of infection. Defensins are AMPs that act primarily by disrupting the integrity of cell membranes of invasive microbes. We previously showed that defensins from the tick Ixodes ricinus inhibited significantly the growth of P. falciparum in vitro, a property that was conserved during evolution. Here, we tested the activity of three I. ricinus defensins against P. chabaudi in mice. A single dose of defensin (120 μl of 1 mg/ml solution) was administered intravenously to P. chabaudi-infected mice, and the parasitemia was followed for 24 h post-treatment. Defensin treatment inhibited significantly the replication (measured as increases in parasitemia) of P. chabaudi after 1 h and 12 h of treatment. Furthermore, defensin injection was not associated with toxicity. These results agreed with the previous report of antiplasmodial activity of tick defensins against P. falciparum in vitro and justify further studies for the use of tick defensins to control malaria.
Keywords: Female; Disease Models, Animal; myši; Animals; Malaria; Plasmodium; klíště; intravenózní podání; antimalarika; Parasitemia; defensiny; malárie; modely nemocí na zvířatech; Defensins; Mice, Inbred BALB C; Administration, Intravenous; zvířata; Antimalarials; Mice; myši inbrední BALB C; ženské pohlaví; Ixodes; parazitemie